EVALUATION OF THE MERDEKA CURRICULUM AT SMA NEGERI 1 TANJUNGPANDAN, BELITUNG REGENCY - Dian Sundari (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study was conducted to evaluate the implementation of the Emancipated Curriculum at Public Senior High School 1 Tanjung pandan, Belitung Regency, using the CIPP evaluation model. The research employed an evaluative approach based on the CIPP model, which focuses on four key components: context, input, process, and product. The study involved the school principal, five teachers, two students, and one administrative staff member as research subjects. Data were collected through semi-structured interviews, participatory observation, and document analysis, and were analyzed qualitatively using the stages of data condensation, data presentation, and conclusion drawing. The findings revealed that in terms of context, there was substantial support from various stakeholders, although resource readiness remained a challenge. Regarding input, the study found that teacher training still required enhancement. In the process component, student creativity and participation showed improvement, but more effective classroom strategies were necessary. As for product, the Emancipated Curriculum had positively influenced student learning outcomes, although certain areas still needed attention. Overall, the study concludes that while the Emancipated Curriculum has a positive impact, further improvements are needed in teacher training, resource provision, and the implementation of effective strategies. The study recommends developing sustainable training programs, enhancing resource support, and strengthening curriculum implementation strategies.